2017
DOI: 10.1155/2017/5369625
|View full text |Cite
|
Sign up to set email alerts
|

Associations between 18F-FDG-PET, DWI, and DCE Parameters in Patients with Head and Neck Squamous Cell Carcinoma Depend on Tumor Grading

Abstract: Our purpose was to analyze associations between positron emission tomography (PET), diffusion weighted imaging (DWI), and dynamic contrast-enhanced (DCE) imaging in patients with head and neck squamous cell carcinoma (HNSCC). The study involved 34 patients (9 women, 25 men, mean age: 56.7 ± 10.2 years). In all patients a simultaneous 18F-FDG-PET/MR was performed. DWI was obtained by using of an axial EPI sequence. Minimal ADC values (ADCmin), mean ADC values (ADCmean), and maximal ADC values (ADCmax) were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 21 publications
(48 reference statements)
3
47
1
Order By: Relevance
“…Hypoxia may inhibit dividing tumor cells or lead to cell death (increased ADC), due to insufficient oxygen supply, but it may directly induce tumoral progression (high FDG-uptake with reduced apoptosis, high production of VEGF, glycolic enzymes and signaling molecules [12,38]) with radioresistance. This however, was dependent on tumor grading with different relations between parenchyma, stroma and microvascular density [14,39]. Surov et al [14] described that SUV max and SUV mean were correlated with cellularity in advanced stage tumours (G3) and only HIF-1α tended to correlate with FDG-uptake.…”
Section: Tablementioning
confidence: 99%
“…Hypoxia may inhibit dividing tumor cells or lead to cell death (increased ADC), due to insufficient oxygen supply, but it may directly induce tumoral progression (high FDG-uptake with reduced apoptosis, high production of VEGF, glycolic enzymes and signaling molecules [12,38]) with radioresistance. This however, was dependent on tumor grading with different relations between parenchyma, stroma and microvascular density [14,39]. Surov et al [14] described that SUV max and SUV mean were correlated with cellularity in advanced stage tumours (G3) and only HIF-1α tended to correlate with FDG-uptake.…”
Section: Tablementioning
confidence: 99%
“…In our study, the MFA method for T1 measurement, individual AIF, higher temporal resolution and 3-D VOI were applied. These data acquisition and DCE-MRI data analysis methods made our results more reliable than the previous studies, which used the dual ip angle method, population AIF, and temporal resolution of 3.5 ms [8] and 6 ms [16]. Additionally, the pathologic TNM stage was used in our study, which is different from the study by Chikui et al [8], which applied the clinical TNM stage.…”
Section: Study Populationmentioning
confidence: 85%
“…In contrast, Leifels et al reported that the K ep was higher in HNSCC cancers with N2-3 stages; however, no differences were observed in DCE-MRI parameters between T1-2 and T3-4 tumors [16]. In our study, K trans , K ep and V p were found to be lower in pathologic stage III-IV lesions than in stage I-II lesions; these results are similar to that of Chikui et al [8] but different from that of Leifels et al [16]. This discrepancy might be related to the different protocol of DCE-MRI scanning as well as different method of pharmacokinetic analysis.…”
Section: Study Populationmentioning
confidence: 86%
See 2 more Smart Citations